A half‐salamo‐based pyridine‐containing ligand and its novel NiII complexes including different auxiliary ligands: syntheses, structures, fluorescence properties, DFT calculations and Hirshfeld surface analysis. Issue 1 (9th February 2021) - Feng, Tao; Li, Li-Li; Li, Ya-Juan; Dong, Wen-Kui
Abstract : Three novel multinuclear Ni II complexes with a half‐salamo‐based pyridine‐containing ligand have been synthesized and characterized by FT–IR, UV–Vis absorption spectroscopy, X‐ray crystallography, Hirshfeld surface analysis and density functional theory (DFT) calculations. Abstract : Three novel multinuclear Ni II complexes, namely, bisμ‐2‐methoxy‐6‐[8‐(pyridin‐2‐yl)‐3, 6‐dioxa‐2, 7‐diazaocta‐1, 7‐dien‐1‐yl]phenolatobis[thiocyanatonickel(II)], [Ni2 ( L )2 (NCS)2 ], 1, bisμ‐2‐methoxy‐6‐[8‐(pyridin‐2‐yl)‐3, 6‐dioxa‐2, 7‐diazaocta‐1, 7‐dien‐1‐yl]phenolatobis[azidonickel(II)], [Ni2 ( L )2 (N3 )2 ], 2, and catena ‐poly[[2‐methoxy‐6‐[8‐(pyridin‐2‐yl)‐3, 6‐dioxa‐2, 7‐diazaocta‐1, 7‐dien‐1‐yl]phenolatonickel(II)]‐μ‐dicyanamidato], [Ni( L )(dca)] n, 3 dca is dicyanamide, C2 N3, and H L is 2‐methoxy‐6‐[8‐(pyridin‐2‐yl)‐3, 6‐dioxa‐2, 7‐diazaocta‐1, 7‐dien‐1‐yl]phenol, C16 H17 N3 O4 , with a half‐salamo‐based pyridine‐containing H L ligand have been synthesized and characterized by FT–IR, UV–Vis absorption spectroscopy, X‐ray crystallography, Hirshfeld surface analysis and density functional theory (DFT) calculations. The central Ni II ions in complexes 1 –3 are hosted in the half‐salamo‐based N3 O‐donor cavity of the organic ligand. Complex 1 is a centrosymmetric dimer and two [Ni( L )(NCS)] units form a centrosymmetric dimeric structure, which is bridged by two phenolate O atoms. The two N atoms at the axial ends are provided by two NCS − ligands. In complex 1, each Ni II ion has a six‐coordinated octahedral geometry. Complex 2 is similar to 1, but they differ in that the auxiliary NCS − ligand is replaced by N3 − . However, complex 3 is a one‐dimensional coordination polymer constructed from [Ni( L )(dca)] units, which are connected by the auxiliary bidentate dca ligand via N ‐donor atoms. As with complexes 1 and 2, the Ni II ion in 3 has a six‐coordinated octahedral geometry.